Fire Ant Management in Citrus - Diepenbrock, Lauren Marie (EDIS, 2020)
While there are many species of ants in Florida, the invasive fire ant (Solenopsis invicta) is the one most people are familiar with. These ants can be pests in agriculture, landscapes and structures. The pest’s ability to use a variety of habitats and resources makes it challenging to manage. Peer reviewed through UF/IFAS Citrus Research and Education Center; published in Citrus Industry Magazine